Postgraduate Support as the Condition for Graduates’ Dedication to the Profession - Galina Vinokurova; Diana Zhuina; Elena Zorkina (ARPHA Proceedings, 2019)
The urgency of this research is caused by the need of the modern education system for the dedication of psychology, defectology and pedagogy graduates to educational organizations in the country and by immature theoretical, methodological, substantive and technological aspects of the process of postgraduate support. The purpose of this article is introduction of the analysis of university graduates’ support and the description of its psychological-acmeological model. Theoretical analysis, empirical research methods (employment monitoring, questioning), modeling method were chosen as the basic research methods in this work. In the article, the psychological-acmeological model of postgraduate support is introduced. It includes three interrelated blocks: 1) goal-oriented, 2) organizational and developing 3) evaluating and resulting. Besides, the features of these blocks are revealed and the algorithm of the model introduction is developed. The model sets out to support the graduates’ professional becoming, form future specialists’ steady motivation for personal professional development, prepare for professional activity and personal professional self-development, and make students adapt to the profession.